Simple sequence repeat-based mini-core collection for white Guinea yam (Dioscorea rotundata) germplasm - Pachakkil, B.; Yamanaka, S.; Girma Tessema, G.; Matsumoto, R.; Tamiru-Oli, M.; Bhattacharjee, Ranjana; Abberton, Michael T.; Muranaka, S.; Asiedu, R.; Terauchi, R.; Takagi, H. (Wiley, 2021)
A core subset with a small number of accessions representing the genetic diversity of the base collection plays a vital role in facilitating efficient utilization of plant genetic resources. This is particularly relevant for vegetatively propagated large plant size tuber crops with a long growing period, such as white Guinea yam (Dioscorea rotundata Poir.). For the efficient utilization of D. rotundata genetic resources, this study was aimed at developing a mini‐core collection from a core collection of 447 D. rotundata accessions maintained at the International Institute of Tropical Agriculture (IITA). Accordingly, a D. rotundata mini‐core collection representing 102 accessions was selected using 16 simple sequence repeat (SSR) markers, retaining ∼98% of the SSR allelic diversity of the base collection. A similar level of diversity was captured within the mini‐core collection and the base collection with respect to 21 morphological traits, ploidy level, and geographic origin. The mini‐core collection demonstrated a wide range of variation in agronomic traits such as growth period, number of tubers, average tuber weight, and total yield per plant. This variation was considerable when compared with the variation observed for the same traits among the 10 lines or genotypes conventionally used in the breeding program at IITA, which were included in this study as checks. The selected mini‐core accessions could serve as a working collection to broaden the genetic variation for use in practical breeding programs, as well as in future genomic analyses aimed at the genetic improvement of D. rotundata in West Africa.